Optimalisasi Perekonomian Masyarakat Kelurahan Alastuwo dengan Workshop Ecoprint Oleh KKN Aworalastuwo UNISKA - Al-Achtaar, Muhammad Zakki; Shalsabilla, Nazhifa; Khurriyatin, Shinta; Misbak, Muftiali; Pangestu, Anggraini Putri; Irsyad, Fachrulli; Aprilia, Destri; Azmi, Moch. Dimas; Laili, Mita Nur (Penerbit Goodwood, 2025)
Purpose: To improve the existing economy communities in various parts of East Java. For example, Alastuwo Village located in Magetan Regency, East Java, is rich in natural resources and has great potential, such as papaya leaves and cassava leaves, which are suitable for eco-printing using the pounding method. The ecoprinting technique is a natural fabric dyeing technique that is now popular in Indonesia. For this reason, the KKN “Aworalastuwo” team from UNISKA initiated a workshop on ecoprinting to increase the local creativity and economy of Alastuwo Village located in Magetan Regency, East Java. Methodology/approach: This observational study used qualitative methods and was conducted in Alastuwo Village on August 7, 2024, for Posyandu Cadres and PKK Mothers in Alastuwo Village. Results/findings: The activity included socialization and mini-training about ecoprinting with the pounding method, and competition as the final part. This activity is expected to be initiated to create a more sustainable economy in Alastuwo Village. Conclusions: The ecoprint workshop held in Alastuwo Village has become an important breakthrough in optimizing the region’s economy. This is because they look at the reach of natural resources and their big potential, such as papaya and cassava leaves. Limitations: Several technical limitations were observed, including the lack of tools and a smooth and adequate working table. Contribution: This program aimed to improve the knowledge of Posyandu Cadres and PKK mothers about ecoprinting using the pounding method.Moreover, it can inspire the development of a creative economy with natural resources in Alastuwo Village.